2010
DOI: 10.1002/jnr.22429
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐κB/p65 responds to changes in the Notch signaling pathway in murine BV‐2 cells and in amoeboid microglia in postnatal rats treated with the γ‐secretase complex blocker DAPT

et al.

Abstract: Microglial cells constitutively express Notch-1 and nuclear factor-kappaB/p65 (NF-kappaB/p65), and both pathways modulate production of inflammatory mediators. This study sought to determine whether a functional relationship exists between them and, if so, to investigate whether they synergistically regulate common microglial cell functions. By immunofluorescence labeling, real-time polymerase chain reaction (RT-PCR), flow cytometry, and Western blot, BV-2 cells exhibited Notch-1 and NF-kappaB/p65 expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Increasing evidence has demonstrated that microglial activation and the consequent release of proinflammatory and cytotoxic factors such as TNF α , IL-1 β , NO, and prostaglandin E synthase 2 (PGE 2 ) are thought to contribute to the neurodegenerative diseases [1315]. Analysis of postmortem brains showed that the increased levels of proinflammatory mediators were investigated in patients with neurological disorders [16].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that microglial activation and the consequent release of proinflammatory and cytotoxic factors such as TNF α , IL-1 β , NO, and prostaglandin E synthase 2 (PGE 2 ) are thought to contribute to the neurodegenerative diseases [1315]. Analysis of postmortem brains showed that the increased levels of proinflammatory mediators were investigated in patients with neurological disorders [16].…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo treatment, mice were subcutaneously injected with γ-secretase inhibitor, DAPT in a range of doses (0, 10, 50, 100 and 200 mg/kg, Tocris, R&D, Minneapolis, MN) daily for 2 days followed by bone marrow cell isolation on day 3 (2527). For TNF-α treatment, a single injection (100 µg/kg) of mouse recombinant TNF-α(Peprotech, Rocky Hill, NJ) was given by intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Although activated microglia scavenge dead cells from the CNS and secrete different neurotrophic factors for neuronal survival [2], [3], it is believed that severe activation causes various autoimmune responses leading to neuronal death and brain injury [4], [5]. Activation of microglia and consequent release of proinflammatory and/or cytotoxic factors such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), nitric oxide (NO), prostaglandin E2 (PGE2), reactive oxygen species (ROS), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) are believed to contribute to neuronal damage, particularly in neurodegenerative diseases [6], [7], [8], [9]. Subsequently, the damaged neurons release toxic soluble factors, which in turn induce microglial activation termed as reactive microgliosis [10].…”
Section: Introductionmentioning
confidence: 99%